Europe and Central Asia Economic Update, May 2018 : Cryptocurrencies and Blockchain - World Bank (Washington, DC: World Bank, 2018)
With growth in Europe and Central Asia likely at its peak, this report addresses two questions. How well is the region prepared for an expected slowdown? How well has the economic upswing been used to adjust to the digital revolution? The report specifically focuses on cryptocurrency and blockchain activities in the region.